2022
DOI: 10.3390/plants11151928
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of R2R3-MYB Transcription Factor and Expression Analysis under Abiotic Stress in Rice

Abstract: The myeloblastosis (MYB) family comprises a large group of transcription factors (TFs) that has a variety of functions. Among them, the R2R3-MYB type of proteins are the largest group in plants, which are involved in controlling various biological processes such as plant growth and development, physiological metabolism, defense, and responses to abiotic and biotic stresses. In this study, bioinformatics was adopted to conduct genome-wide identification of the R2R3-MYB TFs in rice. We identified 190 MYB TFs (99… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 57 publications
(63 reference statements)
1
12
0
Order By: Relevance
“…6 ). The number of R2R3-MYB genes was lower than that of Arabidopsis (126) [ 39 ], rice (99) [ 40 ], impatiens (73) [ 41 ], Chrysanthemum nankingense (183) [ 42 ], and Casuarina equisetifolia (107) [ 43 ], but it was equivalent to the reported number in Morinda officinalis (51) [ 44 ] and Bothriochloa ischaemum (43) [ 45 ] (Fig. 7 ).…”
Section: Discussionmentioning
confidence: 85%
“…6 ). The number of R2R3-MYB genes was lower than that of Arabidopsis (126) [ 39 ], rice (99) [ 40 ], impatiens (73) [ 41 ], Chrysanthemum nankingense (183) [ 42 ], and Casuarina equisetifolia (107) [ 43 ], but it was equivalent to the reported number in Morinda officinalis (51) [ 44 ] and Bothriochloa ischaemum (43) [ 45 ] (Fig. 7 ).…”
Section: Discussionmentioning
confidence: 85%
“…In this study, 12 ClHSP70s were identified in watermelon, which was similar to the number in cucumber (13) and grapevine (15), but less than that in tomato (19), maize (28) and rice (31) ( Figure 3 ; Supplementary Table S1 ). This difference may be related to their genome sizes or evolutionary diversities ( Sung et al, 2001 ; Zhang et al, 2015 ; Guo et al, 2016 ; Kang et al, 2022 ). Gene structure and phylogenetic tree were helpful to analyze the evolutionary relationship among genes( Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gene structure is of great significance to the study of gene evolution [49]. The rearrangements and fusions of different chromosomal fragments may result in the gain or loss of an exon or intron, which play an important role in the diversification of multi-gene families [45].…”
Section: Identification and Analysis Of Gst Genes In Foxtail Milletmentioning
confidence: 99%